SMART TOURISM MARKETING, DIGITAL EXPERIENCE, AND DESTINATION TRUST AS DRIVERS OF TOURIST REVISIT INTENTION: EVIDENCE FROM CONSERVATION-BASED TOURISM IN PANDEGLANG - Asep Syiarudin; Irma Yunita; Bachtiar Rifai; Dewi Rahmi Fauziah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study aims to analyze the effect of Smart Tourism Marketing on Tourist Revisit Intention through Digital Experience and Destination Trust within the context of sustainable tourism. The research was conducted among tourists visiting conservation-based tourism destinations in Pandeglang Regency. A quantitative research method was employed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. Data were collected through questionnaires distributed to 240 tourists who had previously visited tourism destinations in the research area. The results indicate that Smart Tourism Marketing has a positive and significant effect on Digital Experience. Digital Experience is also found to have a positive and significant effect on both Destination Trust and Tourist Revisit Intention. Furthermore, Destination Trust has a positive and significant effect on Tourist Revisit Intention and emerges as the most dominant factor in enhancing tourists’ intention to revisit. However, Smart Tourism Marketing does not have a significant direct effect on Tourist Revisit Intention. The mediation analysis reveals that Digital Experience and Destination Trust are able to mediate the relationship between Smart Tourism Marketing and Tourist Revisit Intention. The findings imply that the development of smart tourism should focus on improving the quality of tourists’ digital experiences and strengthening their trust in destinations. Therefore, destination managers should enhance digital services, platform interactivity, information quality, and the image of destinations as trustworthy and sustainable tourism destinations. ABSTRAK Penelitian ini bertujuan untuk menganalisis pengaruh Smart Tourism Marketing terhadap Tourist Revisit Intention melalui Digital Experience dan Destination Trust dalam konteks sustainable tourism. Penelitian dilakukan pada wisatawan destinasi wisata berbasis konservasi di Kabupaten Pandeglang. Metode penelitian yang digunakan adalah kuantitatif dengan pendekatan Structural Equation Modeling–Partial Least Square (SEM-PLS). Data dikumpulkan melalui penyebaran kuesioner kepada 240 wisatawan yang pernah mengunjungi destinasi wisata di lokasi penelitian. Hasil penelitian menunjukkan bahwa Smart Tourism Marketing berpengaruh positif dan signifikan terhadap Digital Experience. Digital Experience juga terbukti berpengaruh positif dan signifikan terhadap Destination Trust dan Tourist Revisit Intention. Selanjutnya, Destination Trust berpengaruh positif dan signifikan terhadap Tourist Revisit Intention serta menjadi faktor paling dominan dalam meningkatkan niat kunjungan ulang wisatawan. Namun, Smart Tourism Marketing tidak berpengaruh signifikan secara langsung terhadap Tourist Revisit Intention. Hasil pengujian mediasi menunjukkan bahwa Digital Experience dan Destination Trust mampu memediasi hubungan antara Smart Tourism Marketing dan Tourist Revisit Intention. Implikasi penelitian ini menunjukkan bahwa pengembangan smart tourism perlu diarahkan pada peningkatan kualitas pengalaman digital dan kepercayaan wisatawan terhadap destinasi. Oleh karena itu, pengelola destinasi perlu memperkuat layanan digital, interaktivitas platform, kualitas informasi, serta citra destinasi yang terpercaya dan berkelanjutan.